2004
DOI: 10.1073/pnas.0406985101
|View full text |Cite
|
Sign up to set email alerts
|

Coding sequences of functioning human genes derived entirely from mobile element sequences

Abstract: Among all of the many examples of mobile elements or ''parasitic sequences'' that affect the function of the human genome, this paper describes several examples of functioning genes whose sequences have been almost completely derived from mobile elements. There are many examples where the synthetic coding sequences of observed mRNA sequences are made up of mobile element sequences, to an extent of 80% or more of the length of the coding sequences. In the examples described here, the genes have named functions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0
1

Year Published

2006
2006
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 30 publications
0
41
0
1
Order By: Relevance
“…In general, the amino acid sequence relationships are weak but significant. The average relationships show larger divergence than observed for the six genes previously identified that showed relatively precise relationships over most of their length (5). Because of the length of Table 3, the cases of genes with multiple transcript variants (tv) have been reduced to a single example.…”
Section: Comparison Of Three Methods Of Detecting Te Sequences In Humanmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the amino acid sequence relationships are weak but significant. The average relationships show larger divergence than observed for the six genes previously identified that showed relatively precise relationships over most of their length (5). Because of the length of Table 3, the cases of genes with multiple transcript variants (tv) have been reduced to a single example.…”
Section: Comparison Of Three Methods Of Detecting Te Sequences In Humanmentioning
confidence: 99%
“…The test is whether amino acid sequence similarities to human proteins are found. It turns out that these probes are more effective in finding TE sequence relationships to coding sequences than the previously used DNA sequence methods (1)(2)(3)(4)(5). The amino acid sequence probes identify about six times as many as the DNA sequence searches, and the regions of sequence similarity are much longer.…”
mentioning
confidence: 99%
“…Despite (or because of) their selfish nature, transposable elements have had a considerable impact on the evolution of their host genomes; for example, as a result of insertional mutagenesis or by promoting genomic rearrangements (12,13). In this study, we investigated another process by which mobile elements can impact their host genomes, often referred to as ''molecular domestication,'' whereby their coding sequences are recruited to serve a cellular function in their host genomes (4)(5)(6)(7)(8)(9). Specifically, we reconstructed the evolutionary steps leading to the birth of SETMAR, a new chimeric primate gene located on human chromosome 3p26 (14).…”
mentioning
confidence: 99%
“…A much less understood, yet ostensibly recurrent, source of genetic innovation is the recycling of coding material from selfish mobile genetic elements (4)(5)(6)(7)(8)(9). Mobile or transposable elements are ''jumping genes,'' pieces of DNA that can move and replicate within the genomes of virtually all living organisms (10).…”
mentioning
confidence: 99%
“…Lo que resulta desconcertante ---- es que cuando en los artículos sobre su actividad genética se ha planteado la disyuntiva de si los elementos móviles provienen de virus o es a la inversa, ambas alternativas se contemplan como probables 72 , sin definirse por ninguna como si el significado de la una y la otra no fueran abismalmente distintos. Pero si asumimos lo que parece evidente, es decir, que en un sentido genéri-co, los transposones deriven de virus y los retrotransposones de retrovirus, la contribución de los virus a la construcción de los genomas ha sido, por fuerza, la absolutamente mayoritaria 73 . Repitamos los cálculos: Si hemos de creer los resultados de la secuenciación de la fracción codificante de proteínas, que constituye el 1,5% del total del Genoma humano, además de 223 genes identificados como de origen bacteriano (aunque posiblemente sean más), hasta el 50% de sus secuencias están formadas por elementos móviles, por encima del 10% son virus endógenos y «Mucho del restante ADN único debe también ser derivado de copias de antiguos elementos transponibles que han divergido demasiado para ser reconocibles como tales» 74 .…”
Section: Sobre La «Integración De Sistemas Complejos»unclassified